ANTARA CINTA DAN TEKANAN SOSIAL: FAKTOR PENDORONG PERKAWINAN USIA MUDA DALAM MASYARAKAT - Ririn Maesaroh; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
Child marriage is a complex social phenomenon and is influenced by a variety of factors, including social pressures, economic conditions, cultural norms, and media influences. This study aims to analyze the main factors that drive early marriage and its impact on the lives of individuals and society. Based on various studies that have been conducted, it is found that social pressure from the family and the surrounding environment plays a big role in encouraging individuals to marry at a young age, especially for women. In addition, difficult economic conditions often make early marriage seen as a solution to reduce financial burden, especally for women, which leads to limited employment opportunities and financial dependence. In terms of health, teenage pregnancy has a high risk to both mother and baby, including medical complications and a higher mortality rate. Therefore, it is important for the public and the government to increase education about the risks of early marriage and provide policy support that can prevent it. With a better understanding, it is hoped that individuals can make more mature decisions before entering family married life. From a psychological perspective, couples who marry at a young age are more prone to experiencing domestic conflicts due to a lack of emotional readiness and experience in managing long-term relationships. Another negative impact is the inhibition of education and provide policy support that can prevent it. With a better understanding, it is hoped that individuals can make more mature decisions before entering family married life. From a psychological perspective, couples who marry at a young age are more prone to experiencing domestic conflicts due to a lack of emotional readiness and experience in managing long-term relationships. Another negative impact is the inhibition of education